Eksistensu Grup Randai Sinar Tampalo Nagari Padang Laweh Kabupaten Sijunjung (2002-2013) - -, Dafrianto - (Pendidikan Sejarah, 2014)
In this research describe about existence of Randai Group Sinar Tamplao Nagari Padang Laweh Sijunjung regency from the year 2002-2013. in this study discuss about how the standing and popularity. Randai Group Sinar Tamplao found in Nagari Padang Laweh, this Randai haas a good performance, so that Randai Group Sinar Tamplao get the trustÂ of the district Sijunjung to show of the even in inside and outside Sijunjung regency. Moreover Randai Group Sinar Tamplao have existence till now, although many foreign cultures are coming in this study the reseacher used historical method. Firstly , the researcherÂ colect the data from the written and oral sources. for the written sources get from documents, archives,and also in the library about Randai Group Sinar Tamplao. for the oral sources, interview with the leadership, staff and members of Randai Group Sinar Tamplao.Secondly, the from of source criticism that testing and selection of the data collected to see the level of authenticity (external critism)and test information, which is contained in the source (international criticism).